A constructivist multi-criteria decision aid approach for performance evaluation of the supply chain management of public health care : construction of an evaluation model - Marube, Newton Nyamasege (2019)
Society has increasingly demanded efficient public services and of better quality. The current public administration has the challenge of meeting these requirements, for which it has increasingly been adopting practices and methodologies used in the private sector. In this context, performance evaluation emerges as an important management tool capable of helping to improve the public service. Supply chain operation costs currently account for up to 45% of the annual operating expenses of health care organizations. Performance evaluation and its application in specific functional areas, such as Supply Chain Management (SCM), can provide an opportunity to curtail the ever-increasing health care costs. An efficient supply chain management creates value for both organizations and for their various partners who interact throughout the global supply chain. The objective of this study is to build a performance evaluation model of the supply chain management of a public teaching hospital. To achieve this goal, the Multicriteria Decision Aid - Constructivist methodology (MCDA-C) was selected. Through a structured interview with the HU-FURG/EBSERH administrative manager, 160 criteria were identified as relevant and sufficient to evaluate the performance of the supply chain management. These criteria originated from eleven areas of concern, namely: "Administration" , "Budget and Finance", "Hospital Infrastructure", "Information technology", "Teaching", "Purchases", "Logistics", "Politics", "Legislation", "Planning", and "Human Resources management". In addition, the application of the result of this research made it possible to carry out a global assessment of the current situation, on a scale of 0 to 100, with the object of study reaching a value of 51.55. Based on the results obtained through the determination of the compensation rates and the overall assessment of the model, improvements were proposed to improve the performance of aspects at compromising levels and the implementation of the proposed improvements actions will allow the performance of the supply chain management to increase from 51.55 to 76.25 points. It is emphasized that the present study is based on the construction of a performance evaluation tool from a constructivist point of view, based mainly on the visions, beliefs, contexts and opinions of the actors involved and not on specialists or alternatives given by scientific literature.